Processing and extracting data from Dicionário Aberto - Simões, Alberto (2010)
Synonyms dictionaries are useful resources for natural language processing. Unfortunately their availability in digital format is limited, as publishing companies do not release their dictionaries in open digital formats. Dicionário-Aberto is an open and free digital synonyms dictionary for the Portuguese language. It is under public domain which makes it usable for any task. Synonyms dictionaries are commonly used for the extraction of relations between words, constructing structures similar to WordNet, or just the extraction of lists of words of specific type. This article presents Dicionário-Aberto, discusses its characteristics and the type of information present on it. Then, we describe an API to help on processing Dicionário-Aberto without the need to tackle with the dictionary format. Finally, we analyze the results on some data extraction experiments.